Design and performance of a threshold-based load balancing scheme in an ATM switch. - Chowdhury, Shyamal (Computer networks and ISDN systems.)
We consider an ATM switch consisting of a number of output buffered ATM switch elements operating in paralle. Such an architecture may lead to uneven distribution of cells over the parallel switch element buffers, if no modifications